2004
DOI: 10.1099/vir.0.79785-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the prion precursor functional gene but not the pseudogene are associated with susceptibility to chronic wasting disease in white-tailed deer

Abstract: Chronic wasting disease (CWD) status and PrP genotypes were determined for a group of 133 wild white-tailed deer in a 780 acre enclosure in western Nebraska, USA. Approximately half of the deer tested showed evidence of PrP d in the brainstem or lymphoid tissues. Four PRNP alleles encoding amino acid substitutions were identified, with substitutions at residues 95 (QRH), 96 (GRS) or 116 (ARG), each with serine (S) at residue 138. In addition, a processed pseudogene with two alleles encoding five or six copies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
194
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(205 citation statements)
references
References 49 publications
7
194
4
Order By: Relevance
“…A 625 bp region of PRNP that codes amino acids 21 to 227 was amplified by polymerase chain reaction (PCR) using previously published primers CWD-13 and CWD-LA [62] or primers 223 and 224 [37]. Amplification was performed in 25 ul reaction volumes following previously published protocols [34,35,62].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 625 bp region of PRNP that codes amino acids 21 to 227 was amplified by polymerase chain reaction (PCR) using previously published primers CWD-13 and CWD-LA [62] or primers 223 and 224 [37]. Amplification was performed in 25 ul reaction volumes following previously published protocols [34,35,62].…”
Section: Methodsmentioning
confidence: 99%
“…Sequences were checked for the absence of the aa138N mutation to ensure that all sequences were PRNP and not the processed pseudogene. [38] If aa138N was detected with primers CWD-13 and CWD-LA, then the sequence was verified with primers 223 and 224, which were specifically designed to only amplify the functional gene [37] Though it is possible that this mutation could also occur in the functional gene, we did not observe aa138N in any deer when both primer sets were used.…”
Section: Methodsmentioning
confidence: 99%
“…The data suggested that the polymorphisms Q95H and G96S reduce the risk of infection. Homozygote SS 96 as well as heterozygote GS 96 and GH 95 deer are underrepresented in CWD-affected populations [55,73]. CWD in mule deer was also shown to have a genetic component with the polymorphism S225F.…”
Section: Chronic Wasting Disease In Deermentioning
confidence: 97%
“…This model assumes uniform exposure of the population to the TSE agent, which may be a special problem when the exposure of free-ranging populations is investigated. Even so, a statistical significant bias in the PrP genotypes between CWD-affected and healthy white-tailed deer has been found in captive [73] and free-ranging populations [55]. The data suggested that the polymorphisms Q95H and G96S reduce the risk of infection.…”
Section: Chronic Wasting Disease In Deermentioning
confidence: 99%
“…It is possible, however, that the tg(CerPrP96S) mice may be converted by deer CWD derived from an animal that was SS homozygous at codon 96. In naturally infected white-tailed deer, deer that expressed 96SS PrP had a lower risk for CWD infection, but were not resistant, since at least three of 7350 CWD infected deer were positive for PrP Sc in brain [36,59]. Other studies suggest that the 96S allele delays CWD disease progression [95].…”
Section: The Cervid Prnp Genementioning
confidence: 99%